Mappae mundi : humans and their habitats in a long-term socio-ecological perspective : myths, maps and models - De Vries, Bert; Goudsblom, Johan (Amsterdam University Press, 2003)
Never before in human society has the interaction of people and their natural environment been so complex. It is precisely this diversity that creates a need for a synthesis that transcends the boundaries of traditional academic fields. "Mappae Mundi.